The Forms Of Notary Public Responsibilities Regarding False Statements In Land Deed Making - Fitri Nabilah, Hasna; Saptanti, Noor; Mayastuti, Anti (CV. Inara, 2024)
A Notary Public, as a public official authorized to create deeds related to land, must have specific expertise in the field of land to ensure that the deeds created do not cause issues in the future. If problems arise due to negligence on the part of the Notary Public, the deed may only have legal validity as an underhand deed. The purpose of this study is to identify the forms of accountability for Notary Publics for their negligence in creating land sale deeds based on false information. This research employs a normative legal research method to examine and analyze legal norms and the Verdict of the District Court Number 51/Pid.B/2022/PN.Bla. The findings of this research are the forms of Notary Public responsibility for deeds annulled by the court related to the case in this study, including: a) administrative sanctions, such as article 13 of Ministerial Regulation of ATR/BPN No. 2/2018, which involves temporary suspension for up to 1 (one) year and imposition of administrative fines; b) civil sanctions, such as Article 1365 of the Civil Code, which involves reimbursement of costs, compensation, and interest; and c) criminal sanctions, such as article 263 of the Penal Code (forgery of documents) carrying a maximum prison sentence of six years, and Article 264 paragraph (1) of the Penal Code (forgery of authentic deeds) carrying a maximum prison sentence of eight years.